Pengaruh Model Pembelajaran TGT Berbantuan E-LKPD Berbasis Teka-Teki Silang terhadap Minat, Keaktifan, dan Hasil Belajar Siswa - Chatryn Joice Elisabet Panjaitan; Herbert Sipahutar (Biosfer: Jurnal Pendidikan Biologi, 2026)
This study aims to determine the effect of the Team Games Tournament (TGT) learning with crossword puzzles-based E-student worksheet on students’ learning interest, activity, and cognitive outcomes on the ecosystem material. This research is a quasi-experimental study using a pretest-posttest control group design. The subjects consisted of two classes: class X-2 (experimental) taught using the TGT model with crossword puzzles-based E-student worksheet, and class X-3 (control) taught using the Direct Instruction model. The TGT syntax included class presentation, team formation, games, tournament, and team recognition, while the Direct Instruction syntax included presentation of objectives and motivation, material delivery, guided practice, feedback, and independent practice. Data were collected using questionnaires (learning interest), observation sheets (learning activity), and tests (learning outcomes). The data obtained were analyzed using an independent sample t-test, which showed a significance value lower than 0.05. Students in the experimental class showed higher learning interest (71.2% > 58.9%), greater learning activity (81.15% > 59.04%), and higher cognitive outcomes (83.06 > 70.56) compared to the control class. It can be concluded that the TGT model with crossword puzzles-based E-student worksheet has a significant effect on improving students’ learning interest, activity, and cognitive outcomes. Teachers are encouraged to apply this model as a student-centered strategy to improve the quality of biology learning and to use similar interactive media to create more engaging and collaborative learning experiences.